Applying Complex Network and Cell-Cell Communication Network Diagram Methods to Explore the Key Cytokines and Immune Cells in Local Acupoint Involved in Acupuncture Treating Inflammatory Pain. (29th July 2020) - Zhang, Kuo; Zhao, Xue; Ding, Shasha; Liu, Yangyang; Xu, Yuan; Yan, Yawen; Hong, Shouhai; Yang, Fuming; Wang, Shenjun; Xu, Zhifang; Guo, Yongming; Guo, Yi; et al.
Abstract : Manual acupuncture (MA) can effectively treat a variety of diseases, but its specific mechanism remains unclear. The "acupoint network" activated by MA participates in MA signal transduction, in which immune-related cells and cytokines play an important role. However, which cells and cytokines in the acupoint have changed after MA? What is the network relationship between them? Which cells and cytokines may play the most important role in MA effect? These problems are unclear. In this study, on the basis of affirming the analgesic, detumescence, and anti-inflammatory effect of MA, the concentration of 24 cytokines in ST36 acupoint in rats with inflammatory pain after MA treatment was detected by multiplex immunoassay technology. Then, using statistical and complex network and cell-cell communication (CCC) network diagram method to analyze the detected data depicts the network relationship between the cytokines and related cells objectively and establishes cytokine connection network and CCC network, respectively. The results showed that MA reinforced communication intensity between cells while reducing the overall correlation intensity. On this basis, the key cytokines and key cells at three MA time-points were screened out, cytokines IL-6, MCP-1, fibroblasts cell, and monocyte macrophage screened by the three methods at three MA time-points might be the key cytokines or key cells. After that, we detected the macrophages in ST36 acupoint by flow cytometry and immunofluorescence and found that the relative amount of macrophages increased significantly after MA, especially the macrophage of the dermis of skin. This study provided a basis for revealing the initiated mechanism of MA effect.